2016
DOI: 10.1021/acsnano.6b03835
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and in Vivo Mechanism of Bone Tumor Inhibition by Selenium-Doped Bone Mineral Nanoparticles

Abstract: Biocompatible tissue-borne crystalline nanoparticles releasing anticancer therapeutic inorganic elements are intriguing therapeutics holding the promise for both tissue repair and cancer therapy. However, how the therapeutic inorganic elements released from the lattice of such nanoparticles induce tumor inhibition remains unclear. Here we use selenium-doped hydroxyapatite nanoparticles (Se-HANs), which could potentially fill the bone defect generated from bone tumor removal while killing residual tumor cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
148
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(156 citation statements)
references
References 53 publications
6
148
0
2
Order By: Relevance
“…Briefly, PCL (Mw = 50,000) (Daigang Biomaterial Co., Ltd, China) was dissolved in dichloromethane. HA nanoparticles with the size distribution of 80–100 nm were synthesized using previously published protocol [3234]), and dispersed sufficiently in ethyl alcohol by ultrasonication. The two solutions were mixed sufficiently and added dropwise into a solution of 1.5% (w/v) poly(vinyl alcohol).…”
Section: Methodsmentioning
confidence: 99%
“…Briefly, PCL (Mw = 50,000) (Daigang Biomaterial Co., Ltd, China) was dissolved in dichloromethane. HA nanoparticles with the size distribution of 80–100 nm were synthesized using previously published protocol [3234]), and dispersed sufficiently in ethyl alcohol by ultrasonication. The two solutions were mixed sufficiently and added dropwise into a solution of 1.5% (w/v) poly(vinyl alcohol).…”
Section: Methodsmentioning
confidence: 99%
“…HA doped with selenium ions can be obtained in two ways: through synthesis, during which ions are incorporated into the HA structure [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47], or by ion exchange, where soaking in a selenium salt solution results in the exchange of ions in the HA structure [47].…”
Section: Synthesis Of Hydroxyapatites Doped With Selenite and Selenatmentioning
confidence: 99%
“…The selenium nanoparticle (SeNP), which is one form of elemental selenium (Se0), has lower toxicity and better absorption and it is most effective when provided to broiler chicken under oxidative stress with the same dose but different sources of Se (organic, inorganic and nano-Se) [28]. According to some studies, the size of SeNPs synthesized by microorganisms has mostly been between 20 and 300 nm [20,26,27], and the diameter of the SeNPs in this research was 50 to 110 nm, which is consistent with previous research.…”
Section: Discussionmentioning
confidence: 99%
“…Wang et al [20] found Se-HANs induced apoptosis of tumor cells by an inherent caspase-dependent apoptosis pathway synergistically orchestrated with the generation of reactive oxygen species. In addition, another research reported that selenite-doped bone mineral nanoparticles can retard the growth of osteosarcoma in a nude mice model [21].…”
Section: Introductionmentioning
confidence: 99%